Molecular characterization of accripin11, a soluble shell protein with an acidic C‐terminus, identified in the prismatic layer of the Mediterranean fan mussel Pinna nobilis (Bivalvia, Pteriomorphia). Issue 1 (3rd December 2022) - Khurshid, Benazir; Jackson, Daniel J.; Engilberge, Sylvain; Motreuil, Sébastien; Broussard, Cédric; Thomas, Jérôme; Immel, Françoise; Harrington, Matthew J.; Crowley, Peter B.; Vielzeuf, Daniel; Perrin, Jonathan; Marin, Frédéric
Abstract : We have identified a novel shell protein, accripin11, as a major soluble component of the calcitic prisms of the fan mussel Pinna nobilis . Initially retrieved from a cDNA library, its full sequence is confirmed here by transcriptomic and proteomic approaches. The sequence of the mature protein is 103 residues with a theoretical molecular weight of 11 kDa and is moderately acidic (pI 6.74) except for its C‐terminus which is highly enriched in aspartic acid. The protein exhibits a peculiar cysteine pattern in its central domain. The full sequence shares similarity with six other uncharacterized molluscan shell proteins from the orders Ostreida, Pteriida and Mytilida, all of which are pteriomorphids and produce a phylogenetically restricted pattern of nacro‐prismatic shell microstructures. This suggests that accripin11 is a member of a family of clade‐specific shell proteins. A 3D model of accripin11 was predicted with AlphaFold2, indicating that it possesses three short alpha helices and a disordered C‐terminus. Recombinant accripin11 was tested in vitro for its ability to influence the crystallization of CaCO3, while a polyclonal antibody was able to locate accripin11 to prismatic extracts, particularly in the acetic acid‐soluble matrix. The putative functions of accripin11 are further discussed in relation to shell biomineralization. Abstract : Accripin11, a novel 11 kDa protein exhibiting a peculiar cysteine pattern and an acidic disordered C‐terminus, was identified in the outer shell layer of the Mediterranean fan mussel, Pinna nobilis . It is a member of a protein family restricted to Pteriomorphia bivalves. Accripin11 interacts with the precipitation of CaCO3 and is presumably involved in the biomineralization of the shell prismatic microstructure.